Repetitive arm functional tasks after stroke (RAFTAS): a pilot randomised controlled trial. Issue 1 (December 2016) - Brkic, Lianne; Shaw, Lisa; van Wijck, Frederike; Francis, Richard; Price, Christopher; Forster, Anne; Langhorne, Peter; Watkins, Caroline; Rodgers, Helen
Abstract Background Repetitive functional task practise (RFTP) is a promising treatment to improve upper limb recovery following stroke. We report the findings of a study to determine the feasibility of a multi-centre randomised controlled trial to evaluate this intervention. Methods A pilot randomised controlled trial recruited patients with new reduced upper limb function within 14 days of acute stroke from three stroke units. Participants were randomised to receive a four week upper limb RFTP therapy programme consisting of goal setting, independent activity practise, and twice weekly therapy reviews in addition to usual post stroke rehabilitation, or usual post stroke rehabilitation. The recruitment rate; adherence to the RFTP therapy programme; usual post stroke rehabilitation received; attrition rate; data quality; success of outcome assessor blinding; adverse events; and the views of study participants and therapists about the intervention were recorded. Results Fifty five eligible patients were identified, 4-6 % of patients screened at each site. Twenty four patients participated in the pilot study. Two study sites met the recruitment target of 1–2 participants per month. The median number of face to face therapy sessions received was 6 [IQR 3–8]. The median number of daily repetitions of activities recorded was 80 [IQR 39–80]. Data about usual post stroke rehabilitation were available for 18/24 (75 %). Outcome data were available for 22/24 (92 %) at one month and 20/24 (83 %) at three months. Outcome assessors were unblinded to participant group allocation for 11/22 (50 %) at one month and 6/20 (30 %) at three months. Four adverse events were considered serious as they resulted in hospitalisation. None were related to study treatment. Feedback from patients and therapists about the RFTP programme was mainly positive. Conclusions A multi-centre randomised controlled trial to evaluate an upper limb RFTP therapy programme provided early after stroke is feasible and acceptable to patients and therapists, but there are issues which need to be addressed when designing a Phase III study. A Phase III study will need to monitor and report not only recruitment and attrition but also adherence to the intervention, usual post stroke rehabilitation received, and outcome assessor blinding. Trial registration International Standard Randomised Controlled Trials Number (ISRCTN)58527251